Effect of threeyear fallow with herbaceous cover legumes on soil fertility and sweetpotato production in southeastern Nigeria - Okpara, D.A.; Ikeorgu, J.G.; Njoku, J.C.; Tarawali, G. (2009)
The study, between 1999 and 2003, investigated the effect of a 3-year fallow with leguminous cover crops on soil fertility and sweetpotato production in the lowland humid forest zone of south-eastern Nigeria. The experiment was a 2 × 13 factorial in a randomized complete block design with three replicates. Treatments consisted of two sweetpotato varieties (TIS 87/0087 and TIS 8164) and 13 sources (Aeschynomene histrix. Centrosema brasilianum, Centrosema pascuorum, Chamaecrista rotundifolia, Crotalaria ochroleuca, Lab-lab purpureus, Mucuna deeringiana, Mucuna pruriens, Mucuna veracruz, Pueraria phaseoloides, Stylosan-thes capitata, natural fallow, and natural fallow with NPK fertilizer). Aboveground biomass at 3 months after planting was significantly higher in Mucuna veracruz than in other cover crops except Mucuna deeringiana, Mucuna pruriens, and natural fallow. At 4 years after planting, however, Aeschynomene histrix produced significantly higher biomass than the other cover crops that persisted. Mean soil nitrogen was significantly higher with Centrosema pascuorum than with other legume cover crops and natural fallows except for Ae-schynomene histrix, Mucuna veracrux, Chamaecrista rotundifolia, and Crotalaria ochroleuca. In 2002, shoot dry matter in sweetpotato variety TIS 87/0087 was higher by 37% than in variety TIS 8164 and tuber yield was higher by 68%. On average, tuber yields obtained with NPK fertilizer application were statistically similar to those obtained with Mucuna veracruz, Centrosema pascuorum, Centrosema brasilianum, and natural cover infested with Mimosa invisa but significantly lower in other cover crop fallows. There were no significant inter-actions between sweetpotato variety and the cover crops or NPK on tuber yield. The potassium content of the soil showed a significant positive correlation (r = 0.508, P = 0.214) with tuber yield. The enhanced potassium content of the soil under Mucuna veracruz was therefore reflected in the tuber yield.